ANALISIS FAKTOR YANG MENJADI KEPUTUSAN PEMBELIAN GAS LPG 3 KG (Studi Kasus pada Kp. Pasar Heubeul, Pandeglang) - Rudi Eka Nugraha; Iba Gunawan; Fitri Nurlaili (Jurnal Manajemen dan Bisnis, 2020)
This research aims to analyze the factors that become the decision to buy LPG 3 kg, a case study in Kampung Pasar Heubeul community, Pandeglang. The data used is a questionnaire. The sample studied was 118 respondents. The number of variables studied was 27 variables. Data processed using factor analysis as many as 20 variables that meet the requirements for further analysis. Data obtained from respondents were processed using SPSS 20 for Windows. The results showed that the results of the 20 variables analyzed, the factors that made the purchase decision of LPG 3 Kg consisted of 7 factors, namely Social Factor with eigen value 3,985, Distribution Factor with eigen value 2,307, Price Factor with eigen value 1,772, Product Factor with eigen value value 1,493, Factor 5 enters the product factor with an eigen value 1,282, Factor 6 enters the product factor with an eigen value of 1,176 and Factor 7 enters the distribution factor with an eigen value of 1,125.